PEMILIHAN PEGADAIAN KONVENSIONAL OLEH MASYARAKAT DI KOTA PEKANBARU - Aditya Ulil Mursidin; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Among the interesting phenomena that occur today is the start of the community will be riba. Since the year 2017, then the campaign about usury is done, ranging from lectures in mosques, social media, and large billboards that are scattered at some of the street points of Pekanbaru City, the Da'wah billboards invites people to stay away from riba. This shows the start of the Society of Pekanbaru City will be the danger of riba in life, and this is also driven by the desire of a bertanwitness in accordance with the principle of the rulings in Islam which is of course contrary to Conventional Pawnshops that provide capital rent (interest) to the borrower. Although the people of Pekanbaru have literate about riba, we can not say that there are still many Muslim people who choose to use the service or pawn valuables in the Conventional Pawnshop rather than the Sharia Pawn. The problem is why the Muslim community in the city of Pekanbaru chose the Conventional Pawnshop. Informant of 10 customers of the conventional Pawnshop Pekanbaru city branch is Muslim, in determining the informants the authors studied using accidental sampling technique. Data collection is conducted using observation, interview, and documentation methods. The results of this research show that customers choose Conventional Pawnshops because Conventional Pawnshops has more product variations, the amount of loan funds provided, low capital rental rates, procedures and rapid disbursement of borrowing funds, and ease of transaction requirements. This is followed by the knowledge of customers who know more about Conventional Pawnshop, customers understanding that equates between Conventional and Sharia Pawnshop, as well as weak norms believed by customers. Although the customer knows that borrowing funds in Conventional Pawnshop there are capital leases give rise to usury, but because the norm is weak then for him to do such transactions including things done. Keywords: Conventional Pawnshop Selection, Muslim Society